Disrupted Ankle Control and Spasticity in Persons With Spinal Cord Injury: The Association Between Neurophysiologic Measures and Function. A Scoping Review - Hope, Jasmine M.; Koter, Ryan Z.; Estes, Stephen P.; Field-Fote, Edelle C. (Frontiers in Neurology, 2020)
Control of muscles about the ankle joint is an important component of locomotion and balance that is negatively impacted by spinal cord injury (SCI). Volitional control of the ankle dorsiflexors (DF) is impaired by damage to pathways descending from supraspinal centers. Concurrently, spasticity arising from disrupted organization of spinal reflex circuits, further erodes control. The association between neurophysiological changes (corticospinal and spinal) with volitional ankle control (VAC) and spasticity remains unclear. The goal of this scoping review was to synthesize what is known about how changes in corticospinal transmission and spinal reflex excitability contribute to disrupted ankle control after SCI. We followed published guidelines for conducting a scoping review, appraising studies that contained a measure of corticospinal transmission and/or spinal reflex excitability paired with a measure of VAC and/or spasticity. We examined studies for evidence of a relationship between neurophysiological measures (either corticospinal tract transmission or spinal reflex excitability) with VAC and/or spasticity. Of 1538 records identified, 17 studies were included in the review. Ten of 17 studies investigated spinal reflex excitability, while 7/17 assessed corticospinal tract transmission. Four of the 10 spinal reflex studies examined VAC, while 9/10 examined ankle spasticity. The corticospinal tract transmission studies examined only VAC. While current evidence suggests there is a relationship between neurophysiological measures and ankle function after SCI, more studies are needed. Understanding the relationship between neurophysiology and ankle function is important for advancing therapeutic outcomes after SCI. Future studies to capture an array of corticospinal, spinal, and functional measures are warranted.